Central nervous system metastatic epithelial ovarian cancer. Clinical parameters and prognostic factors: a multicenter study of Anatolian Society of Medical Oncology - Seber, S.; Turkmen, E.; Harputoglu, H.; Yesil, H.; Arpaci, E.; Menekse, S.; Yetisyigit, T. (7847050 Canada Inc, 2017)
Central nervous system (CNS) metastasis is a rare event in the course of late stage epithelial ovarian cancer (EOC); however its incidence is increasing in parallel with prolonged survival of patients. Objective: The authors assessed the clinical parameters and potential prognostic features in patients with CNS metastatic disease. Materials and Methods: Clinical data of the 33 patients from the participating centers were retrospectively collected and analyzed. Median age at the time of CNS metastasis was 57 years. Median time from the diagnosis of primiuy EOC until CNS metastatic disease was 22 months. Nearly half (45.5%) of the patients had single CNS metastatic lesions and all patients in the study group except two received radiotherapy as palliative treatment. Median overall survival (OS) from the time of CNS metastasis was 15 months (0-66). At univariate analysis only number of brain metastatic lesions (p = 0.001) and presence of extracranial disease (p = 0.004) were strongly associated with OS whereas multimodal treatment, size of metastatic lesions, platinum sensitivity, age, grade, and disease stage at presentation were not. Development of CNS metastasis carries a poor prognosis, however patients with single metastatic lesions and only intracranial metastatic disease can have prolonged survival after appropriate palliative management of their disease.
Keywords: Central nervous system epithelial ovarian cancer; Metastasis; Palliative management